Exact representation of piecewise affine functions via neural networks - Schulze Darup, Moritz (2020 European Control Conference (ECC))

Encrypted Cooperative Control Revisited - Alexandru, Andreea B.; Schulze Darup, Moritz; Pappas, George J. (2019 IEEE 58th Conference on Decision and Control (CDC))

Encrypted polynomial control based on tailored two‐party computation - Schulze Darup, Moritz (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Optimal event‐triggered transmission scheduling for privacy‐preserving wireless state estimation - Lu, Jingyi; Leong, Alex S.; Quevedo, Daniel E. (International Journal of Robust and Nonlinear Control)
Keywords: Electrical and Electronic Engineering; Industrial and Manufacturing Engineering; Mechanical Engineering; Aerospace Engineering; Biomedical Engineering; General Chemical Engineering; Control and Systems Engineering

Reflexion von (eigenem oder fremdem) Klassenführungsverhalten angehender Lehrpersonen. Eine Untersuchung im Kontext von Unterrichtssimulationen im Lehramtsstudium. - Stender, Jana; Vogelsang, Christoph; Watson, Christina; Schaper, Niclas (Jahrbuch für Allgemeine Didaktik (JfAD))

Kompetenzentwicklung im bildungswissenschaftlichen Studium: Der Einfluss individueller Voraussetzungen auf die Entwicklung des bildungswissenschaftlichen Wissens angehender Lehrkräfte - Watson, Christina; Stender, Jana; Schaper, Niclas (Zeitschrift für Pädagogische Psychologie)
Zusammenfassung. Längsschnittstudien, die das bildungswissenschaftliche Wissen als Teil der professionellen Kompetenz angehender Lehrkräfte über mehr als zwei Messzeitpunkte erfassen und den Einfluss individueller Eingangsvoraussetzungen auf die Wissensentwicklung untersuchen, stellen nach wie vor ein Forschungsdesiderat dar. Bisherige Studien liefern erste Hinweise darauf, dass individuelle Eingangsvoraussetzungen wie die Abiturnote, pädagogische Vorerfahrungen und Berufswahlmotive im Zusammenhang mit der Wissensentwicklung stehen und günstige Eingangsvoraussetzungen den Entwicklungsverlauf fördern können. Bislang ist unklar, wie sich das Wissen über den gesamten Studienverlauf in den Bachelor-/Master-Strukturen entwickelt. Des Weiteren ist auch unklar, inwieweit bestimmte Eingangsvoraussetzungen langfristige Entwicklungsverläufe erklären können. In der vorliegenden Studie wurden die Daten von 276 Studierenden, dessen Wissen zu fünf Messzeitpunkten erhoben wurde, mit Hilfe latenter Wachstumskurvenmodelle ausgewertet. Die Ergebnisse bestätigten einen Zuwachs des bildungswissenschaftlichen Wissens über den gesamten Studienverlauf. Den größten Wissenszuwachs erfuhren die Studierenden in den ersten zwei Semestern ihres Bachelorstudiums und beim Übergang in das Masterstudium. Des Weiteren konnte der Einfluss von individuellen kognitiven und motivationalen Eingangsvoraussetzungen auf den Leistungszuwachs bestätigt werden. So zeigte sich, dass Studierende, die eine bessere Abiturnote aufwiesen und bereits über eine unterrichtsnahe pädagogische Vorerfahrung verfügten, höhere Wissenszuwächse im Vergleich zu ihren Kommilitoninnen und Kommilitonen erfuhren, die einen schlechteren Abiturnotendurchschnitt hatten. Ebenfalls begünstigte das Motiv „mit Kindern und Jugendlichen arbeiten zu wollen“ die Wissensentwicklung. Die Ergebnisse können insbesondere für die Beratung genutzt werden, um die Motivlagen von Studierenden zu erfassen und sie dafür sensibel zu machen, welche Motivkonstellationen für einen erfolgreichen Studienverlauf günstig erscheinen.

The regularity problem for Lie groups with asymptotic estimate Lie algebras - Hanusch, Maximilian (Indagationes Mathematicae)
Keywords: regularity of Lie groups

The Strong Trotter Property for Locally μ-convex Lie Groups - Hanusch, Maximilian (Journal of Lie Theory)
Keywords: Lie theory; strong Trotter property

Exploring the phenomenological, environmental, and task-related aspects of the Yips in Tennis, Miniature Golf, Darts, and Archery. - Klämpfl, Martin; Lobinger, Babett; Lehmann, Tim (International Journal of Sport Psychology)

Lehre:digital – Erwerb digitaler Lehrkompetenz im fächerübergreifenden Kontext Chemie, Biologie und Physik - Huwer, Johannes; Thyssen, Christoph; Vogelsang, Christoph (Digitale Innovationen und Kompetenzen in der Lehramtsausbildung)

"Jetzt auch noch Werte vermitteln?" - Potentiale und Grenzen der Adaption schuldidaktischer Werkzeuge in der Hochschuldidaktik zur Integration von Wertefragen in die Hochschullehre - Vogelsang, Christoph; Al-Kabbani, Daniel (Hochschuldidaktik als Akteurin der Hochschulentwicklung)

Sichtweisen von Grundschullehrkräften auf die Qualität inklusiven Unterrichts - Görel, Gamze; Finke, Nils; Hellmich, Frank (Diversität und soziale Ungleichheit. Jahrbuch Grundschulforschung)

Integration of Novel Sensors and Machine Learning for Predictive Maintenance in Medium Voltage Switchgear to Enable the Energy and Mobility Revolutions - Hoffmann, Martin W.; Wildermuth, Stephan; Gitzel, Ralf; Boyaci, Aydin; Gebhardt, Jörg; Kaul, Holger; Amihai, Ido; Forg, Bodo; Suriyah, Michael; Leibfried, Thomas; Stich, Volker; Hicking, Jan; et al. (Sensors)
The development of renewable energies and smart mobility has profoundly impacted the future of the distribution grid. An increasing bidirectional energy flow stresses the assets of the distribution grid, especially medium voltage switchgear. This calls for improved maintenance strategies to prevent critical failures. Predictive maintenance, a maintenance strategy relying on current condition data of assets, serves as a guideline. Novel sensors covering thermal, mechanical, and partial discharge aspects of switchgear, enable continuous condition monitoring of some of the most critical assets of the distribution grid. Combined with machine learning algorithms, the demands put on the distribution grid by the energy and mobility revolutions can be handled. In this paper, we review the current state-of-the-art of all aspects of condition monitoring for medium voltage switchgear. Furthermore, we present an approach to develop a predictive maintenance system based on novel sensors and machine learning. We show how the existing medium voltage grid infrastructure can adapt these new needs on an economic scale.
Keywords: Electrical and Electronic Engineering; Biochemistry; Instrumentation; Atomic and Molecular Physics; and Optics; Analytical Chemistry

Science Teaching Processes (strand 3). In Levrini, O. & Tasquier, G. (eds.), The beauty and pleasure of understanding: engaging with contemporary challenges through science education. Electronic Proceedings of the ESERA 2019 Conference.

Development and psychometric evaluation of an instrument measuring subjective definitions of inclusion (FEDI). International Journal of Inclusive Education. - Scheer, D.; Egener, L.; Laubenstein, Désirée; Melzer, C. (In: International Journal of Inclusive Education)

Verknüpfung von Fach- und Sprachlernen im Textilunterricht – Ein Anleitung zur Technik Weben schreiben - Stenzel, Nadja (DaZ Sekundarstufe: Deutsch als Zweitsprache - Konzepte und Materialien)

Characterisation of the PS-PMMA Interfaces in Microphase Separated Block Copolymer Thin Films by Analytical (S)TEM - Bürger, Julius; Kunnathully, Vinay; Kool, Daniel; Lindner, Jörg; Brassat, Katharina (Nanomaterials)
Block copolymer (BCP) self-assembly is a promising tool for next generation lithography as microphase separated polymer domains in thin films can act as templates for surface nanopatterning with sub-20 nm features. The replicated patterns can, however, only be as precise as their templates. Thus, the investigation of the morphology of polymer domains is of great importance. Commonly used analytical techniques (neutron scattering, scanning force microscopy) either lack spatial information or nanoscale resolution. Using advanced analytical (scanning) transmission electron microscopy ((S)TEM), we provide real space information on polymer domain morphology and interfaces between polystyrene (PS) and polymethylmethacrylate (PMMA) in cylinder- and lamellae-forming BCPs at highest resolution. This allows us to correlate the internal structure of polymer domains with line edge roughnesses, interface widths and domain sizes. STEM is employed for high-resolution imaging, electron energy loss spectroscopy and energy filtered TEM (EFTEM) spectroscopic imaging for material identification and EFTEM thickness mapping for visualisation of material densities at defects. The volume fraction of non-phase separated polymer species can be analysed by EFTEM. These methods give new insights into the morphology of polymer domains the exact knowledge of which will allow to improve pattern quality for nanolithography.
Keywords: General Materials Science; General Chemical Engineering

Strain-driven InAs island growth on top of GaAs(111) nanopillars - Riedl, Thomas; Kunnathully, V. S.; Trapp, A.; Langer, T.; Reuter, Dirk; Lindner, Jörg (Physical Review Materials)
Keywords: Physics and Astronomy (miscellaneous); General Materials Science

Influence of lens aberrations, specimen thickness and tilt on differential phase contrast STEM images - Bürger, Julius; Riedl, Thomas; Lindner, Jörg (Ultramicroscopy)
Keywords: Instrumentation; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Digitalisierung ist derzeit ein viel diskutiertes Thema. Mit ihr werden derart tief grei- fende Veränderungen der Gesellschaft und Arbeitswelt erwartet, dass sie häufig als digitale Revolution bezeichnet wird. Gleichzeitig wirft die Auseinandersetzung mit diesen antizipierten Veränderungen viele noch unbeantwortete Fragen auf. Diese umfassen unter anderem Überlegungen hinsichtlich des Substitutionspotenzials menschlicher Arbeit durch die Digitalisierung, die Frage nach der Ausgestaltung der Rolle des Menschen in der Industrie 4.0 und schließlich Erwägungen in Bezug auf die Vorbereitung und Begleitung von Beschäftigten in der digitalen Transformation. Der vorliegende Beitrag gibt Aufschluss über die Dimensionen der Digitalisierung und die derzeit diskutierten Entwicklungslinien; er befasst sich weiterhin mit den sich daraus ergebenden Herausforderungen und Bedeutungen für die industrielle Arbeit und die Beschäftigten. Abschließend werden daraus abzuleitende Implikationen für die berufliche und allgemeine Bildung diskutiert.
Keywords: Digitalisierung; Industrie 4.0; Arbeit 4.0; berufliche Aus- und Weiterbildung; allgemeine Bildung / digitalization; industry 4.0; work 4.0; vocational education and training; general education

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Applicability of molecular statics simulation to partial dislocations in GaAs - Riedl, Thomas; Lindner, Jörg (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Applicability of molecular statics simulation to partial dislocations in GaAs - Riedl, Thomas; Lindner, Jörg (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Mode-locked laser timing jitter limitation in optically enabled frequency-sliced ADCs - Zazzi, Andrea; Müller, Juliana; Gudyriev, Sergiy; Marin-Palomo, Pablo; Fang, Dengyang; Scheytt, Christoph; Koos, Christian; Witzens, Jeremy (21. ITG-Fachtagung Photonische Netze)
Novel analog-to-digital converter (ADC) architectures are motivated by the demand for rising sampling rates and effective number of bits (ENOB). The main limitation on ENOB in purely electrical ADCs lies in the relatively high jitter of oscillators, in the order of a few tens of fs for state-of-the-art components. When compared to the extremely low jitter obtained with best-in-class Ti:sapphire mode-locked lasers (MLL), in the attosecond range, it is apparent that a mixed electrical-optical architecture could significantly improve the converters' ENOB. We model and analyze the ENOB limitations arising from optical sources in optically enabled, spectrally sliced ADCs, after discussing the system architecture and implementation details. The phase noise of the optical carrier, serving for electro-optic signal transduction, is shown not to propagate to the reconstructed digitized signal and therefore not to represent a fundamental limit. The optical phase noise of the MLL used to generate reference tones for individual slices also does not fundamentally impact the converted signal, so long as it remains correlated among all the comb lines. On the other hand, the timing jitter of the MLL, as also reflected in its RF linewidth, is fundamentally limiting the ADC performance, since it is directly mapped as jitter to the converted signal. The hybrid nature of a photonically enabled, spectrally sliced ADC implies the utilization of a number of reduced bandwidth electrical ADCs to convert parallel slices, resulting in the propagation of jitter from the electrical oscillator supplying their clock. Due to the reduced sampling rate of the electrical ADCs, as compared to the overall system, the overall noise performance of the presented architecture is substantially improved with respect to a fully electrical ADC.

Fundamental limitations of spectrally-sliced optically enabled data converters arising from MLL timing jitter - Zazzi, Andrea; Müller, Juliana; Gudyriev, Sergiy; Marin-Palomo, Pablo; Fang, Dengyang; Scheytt, Christoph; Koos, Christian; Witzens, Jeremy (Opt. Express)
The effect of phase noise introduced by optical sources in spectrally-sliced optically enabled DACs and ADCs is modeled and analyzed in detail. In both data converter architectures, a mode-locked laser is assumed to provide an optical comb whose lines are used to either synthesize or analyze individual spectral slices. While the optical phase noise of the central MLL line as well as of other optical carriers used in the analyzed system architectures have a minor impact on the system performance, the RF phase noise of the MLL fundamentally limits it. In particular, the corresponding jitter of the MLL pulse train is transferred almost one-to-one to the system-level timing jitter of the data converters. While MLL phase noise can in principle be tracked and removed by electronic signal processing, this results in electric oscillator phase noise replacing the MLL jitter and is not conducive in systems leveraging the ultra-low jitter of low-noise mode-locked lasers. Precise analytical models are derived and validated by detailed numerical simulations.

28 Gbps Bang-Bang CDR for 100G PSM4 with Independently Tunable Proportional and Integral Parameters of the Loop Filter in 0.25 µm Photonic BiCMOS Technology - Iftekhar, Mohammed; Gudyriev, Sergiy; Scheytt, Christoph (2020 IEEE 20th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems (SiRF))
A 28 Gbps NRZ bang-bang clock and data recovery (CDR) chip for 100G PSM4 is presented. It exhibits an adaptable loop filter transfer function with independently tunable proportional and integral parameters. This allows to optimize the jitter transfer, jitter tolerance, and locking range of the CDR according to system requirements. The CDR represents a key component for a single-chip 8-channel electronic-photonic PSM4 transceiver. A CDR chip was manufactured in a 0.25 μm monolithic photonic BiCMOS technology. The core chip area is 0.51 mm 2 and it dissipates 330 mW from 2.5 V and 3.3 V power supplies.

Analysis and Simulation of a Wireless Phased Array System with Optical Carrier Distribution and an Optical IQ Return Path - Kruse, Stephan; Kress, Christian; Scheytt, Christoph; Kurz, Heiko G.; Schneider, Thomas (GeMiC 2020 - German Microwave Conference)
In this paper we present a new system concept for an optoelectronic wireless phased array system. Like in a conventional phased array system with optical carrier distribution, optical fibers are used to distribute the carrier from the basestation to the wireless frontends. However in contrast to prior concepts, we propose to use an optical IQ return path from the wireless frontends back to the basestation. Furthermore, we reuse the optical carrier signal for the IQ return path which allows to avoid local oscillator lasers in the wireless frontends and reduces the hardware effort significantly. The system concept allows to integrate all components of an optoelectronic wireless frontend in a single chip using silicon photonics technology.

All-optical switching of a dye-doped liquid crystal plasmonic metasurface - Atorf, Bernhard; Mühlenbernd, Holger; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (Optics Express)

Ultra-Low Phase Noise Frequency Synthesis for THz Communications Using Optoelectronic PLLs - Scheytt, Christoph; Wrana, Dominik; Bahmanian, Meysam; Kallfass, Ingmar (2020 Third International Workshop on Mobile Terahertz Systems (IWMTS))
Recently it has been demonstrated that an optoelectronic phase-locked loop (OEPLL) using a mode-locked laser as a reference oscillator achieves significantly lower phase noise than conventional electronic frequency synthesizers. In this paper a concept for an OEPLL-based frequency synthesizer is presented and it is investigated how it can be used as a local oscillator (LO) for THz transceivers in order to improve the signal quality in THz wireless communications. The concept of the OEPLL is presented and it's measured phase noise is compared to the phase noise of a laboratory-grade electronic frequency synthesizer. The measured phase noise spectra of both synthesizers at 10 GHz are then used to model LO phase noise at 320 GHz. Based on models of generic zero-IF transmit and receive frontends, THz signals with different modulation formats and Baud rates are simulated at system level using the modeled LO phase noise for the two LO approaches. Finally, the results are compared.

Praxissemester - Caruso, Carina (Das wissenschaftlich-religionspädagogische Lexikon im Internet)

Der Weg zur Theologie-Professur ist hart – gerade für Religionslehrer! - Caruso, Carina (katholisch.de, Kolumne „Mein Religionsunterricht“.)

Inszenierungen im digitalen Bild. Eine Rekonstruktion der Selfie-Praktiken Jugendlicher mittels der Dokumentarischen Bildinterpretation. - Schwabl, Franziska

Fotografien als Zugang zur Lebenswelt Jugendlicher. Eine Analyse der digitalen Inszenierungspraktiken Jugendlicher im berufsschulischen Übergangssystem. - Schwabl, Franziska (bwp@Berufs-und Wirtschaftspädagogik – online)

Optimierung von Organisationsstrukturen für die emotionale und soziale Entwicklung? Wissenschaftliche Begleitung des Projekts „Geschwisterklassen“ - online. - Scheer, D.; Laubenstein, Désirée

Auswirkungen der Corona-Schulschließungen auf Schülerinnen und Schüler mit und ohne Förderbedarf der emotionalen und sozialen Entwicklung (COFESE) - online. - Scheer, D.; Laubenstein, Désirée

Against All Odds: Tentative Steps Toward Efficient Information Sharing in Groups - Schlangenotto, Darius; Schnedler, Wendelin; Vadovic, Radovan (Games)

Revisiting a Remedy Against Chains of Unkindness - Schnedler, Wendelin; Stephan, Nina Lucia (Schmalenbach Business Review)

Werberecht (Gesetze, Urteile, Fälle und Lösungen, Sprachfassung auf interaktiver CD) 2. Auflage - Krimphove, Dieter

Reverse Factoring: Eine alternative Finanzierungsform in der Praxis - Krimphove, Dieter; Lüke, Christoph (Corporate Finance)

Nachhaltigkeit und Compliance - Krimphove, Dieter (Compliance Berater)

EuGH entscheidet zu Lücken im Europäischen Vorrangsprinzip - Krimphove, Dieter (ArbR - Arbeitsrecht Aktuell)

Designing a Geometry Capstone Course for Student Teachers: Bridging the gap between academic mathematics and school mathematics in the case of congruence - Hoffmann, Max; Biehler, Rolf (INDRUM 2020, Université de Carthage, Université de Montpellier, Sep 2020, Cyberspace (virtually from Bizerte), Tunisia)
At Paderborn University, a new 6th semester geometry-course for upper secondary student teachers has been designed and taught by the first author of this paper. To show links between academic mathematics and school mathematics we established so-called interface weeks. These are weeks during a course in which lecture, exercises and homework focus on topics that are related to the normal canon of content but specially chosen for their relevance in school contexts. In this article, we want to present our design for an interface week on the topic of congruence. In order to do so, we first illustrate how so-called interface aspects are used to systematize the mathematical background of the topic, thus giving future mathematics teachers the chance to act professionally. We then show examples of learning activities and first results of the accompanying research.

Antike und mittelalterliche Grundlagen frühneuzeitlicher Friedensvorstellungen - Kamp, Hermann (Handbuch Frieden im Europa der Frühen Neuzeit / Handbook of Peace in Early Modern Europe)

Culture of Politics in the Middle Ages: Rituals to create and confirm political order - Kamp, Hermann (The Routledge Companion to Cultural History in the Western World)

Einleitung - Kamp, Hermann; Schmitz, Sabine (Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung)

Vom Franzosenfeind zum Fußballfreund. Jan Breydel im Gedächtnis der Belgier, Flamen und Brügger Bürger - Kamp, Hermann (Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung)

Erinnerungsorte in Belgien. Instrumente lokaler, regionaler und nationaler Sinnstiftung

Extending Loyalty Programs with BI Functionalities A Case Study for Brick-and-Mortar Stores - Kucklick, Jan-Peter; Kamm, Michael Reiner; Schneider, Johannes; vom Brocke, Jan (Proceedings of the 53rd Hawaii International Conference on System Sciences)
Effective customer loyalty programs are essential for every company. Small and medium sized brick-and- mortar stores, such as bakeries, butcher and flower shops, often share a common overarching loyalty program, organized by a third-party provider. Furthermore, these small shops have limited resources and often cannot afford complex BI tools. Out of these reasons we investigated how traditional brick-and- mortar stores can benefit from an expansion of service functionalities of a loyalty card provider. To answer this question, we cooperated with a cross-industry customer loyalty program in a polycentric region. The loyalty program was transformed from simple card-based solution to a mobile app for customers and a web- application for shop owners. The new solution offers additional BI services for performing data analytics and strengthening the position of brick-and-mortar stores. Participating shops can work together in order to increase sales and align marketing campaigns. Therefore, shopping data from 12 years, 55 shops, and 19,000 customers was analyzed.
Keywords: brick-and-mortar stores; business intelligence; case study; loyalty program

Human-Machine Learning und Digital Commons. K/Ein Manifest - Weber, Jutta (Das Argument)

Data mining for small shops: Empowering brick-and-mortar stores through BI functionalities of a loyalty program1 - Kamm, Michael Reiner; Kucklick, Jan-Peter; Schneider, Johannes; vom Brocke, Jan (Information Systems Management)
While the analysis and usage of data are increasing in importance, the application of sophisticated BI solutions in small stores is limited by available technical capabilities and financial resources. This study investigates how brick-and-mortar stores can benefit from an expansion of service functionalities of a cross-industry loyalty card provider. Digitalizing the loyalty program created new opportunities, while the analysis of shopping data of 13 years, 19,000 customers, and 55 shops empowered data-based decision support.
Keywords: Customer loyalty; case study; brick-and-mortar stores; business intelligence; loyalty programs